2018
DOI: 10.1177/0959683618798116
|View full text |Cite
|
Sign up to set email alerts
|

Genetic evidence for a western Chinese origin of broomcorn millet (Panicum miliaceum)

Abstract: Broomcorn millet (Panicum miliaceum) is a key domesticated cereal that has been associated with the north China centre of agricultural origins. Early archaeobotanical evidence for this crop has generated two major debates. First, its contested presence in pre-7000 cal. BP sites in eastern Europe has admitted the possibility of a western origin. Second, its occurrence in the 7th and 8th millennia cal. BP in diverse regions of northern China is consistent with several possible origin foci, associated with differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 69 publications
4
32
0
Order By: Relevance
“…ernmost, easternmost, westernmost, and southernmost parts of the Yamnaya range, which yielded similar estimates of speed (SI Appendix, Table S2). The magnitude of the negative correlation coefficients between time and distance from origin can also be used to estimate the point of origin (8,37), assuming a range expansion for the YAM and NEOL ancestries. Indeed, when we altered the point of origin, we found that the most negative correlation coefficients corresponded to Anatolia and the Middle East for the NEOL ancestry and to the Caspian steppe for the YAM ancestry (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ernmost, easternmost, westernmost, and southernmost parts of the Yamnaya range, which yielded similar estimates of speed (SI Appendix, Table S2). The magnitude of the negative correlation coefficients between time and distance from origin can also be used to estimate the point of origin (8,37), assuming a range expansion for the YAM and NEOL ancestries. Indeed, when we altered the point of origin, we found that the most negative correlation coefficients corresponded to Anatolia and the Middle East for the NEOL ancestry and to the Caspian steppe for the YAM ancestry (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the explicit domestication area of broomcorn millet and its spread routes after its domestication remains the fundamentally controversial issue in the domestication study of this cereal. A recent genetic study based on microsatellite and granule-bound starch synthase I (GBSSI) genotype data of cultivated broomcorn millet from pan Eurasian indicated that the Loess Plateau is one of the domestication areas of broomcorn millet, which spread westward via the Inner Asia Mountain Corridor [10]. However, the results did not rule out the possibility of the existence of other domestication areas of broomcorn millet [10].…”
Section: Introductionmentioning
confidence: 98%
“…Our re-examination of Usatovo millet impressions and Usatovo chronology permits more than one narrative. If both Usatovo millet impressions and Usatovo chronology are substantiated, this might indicate either a very early contact between Eurasian communities, or alternatively a domestication event in the west, although the latter is not supported by genetic evidence (Hunt et al 2018). If millet impressions are substantiated while Usatovo chronology is adjusted to accommodate the later dates excluded by Petrenko and Kaiser (2011), the time gap between Usatovo millet impressions and other early direct dated millet findings in the west of Altai might disappear.…”
Section: Resultsmentioning
confidence: 98%